Reviving smallholder hill farming by involving rural youth in food system transformation and promoting community-based agri-ecotourism: A case of Uttarakhand State in North-Western India - Rana, Jai Chand; Bisht, Ishwari Singh (MDPI, 2023)
Until recent decades, labour-intensive subsistence farming was a way of life and livelihood in the hill communities of Uttarakhand, India. However, the nature of agriculture falls far short of the expectations of the main labour force, the rural youth, leading to their mass migration to non-agricultural occupations. The large-scale youth migration has left many hill farming landscapes depopulated and farmlands abandoned. As youth have special stakes in food systems, they must be included in the sustainable transformation of food systems. By doing so, the migration-prone hill region may be transformed into a place where rural youth have more options for work and income. Therefore, the agriculture sector needs to change and develop into a more engaging and youthful workplace. There are opportunities to explore and barriers to be removed. Besides identifying priority research areas on local food systems, in this exploratory research, we investigate opportunities to involve rural young people in the transformation of the food system. We document information by conducting focus group discussion (FGD) meetings in about 100 villages in the Uttarakhand hills, representing all major farming landscapes. This study mainly focuses on improving the production and consumption aspects of local food, which not only benefits the health and wellbeing of local communities but also has many positive economic, social, and environmental effects. In addition, we explore opportunities for reviving mountain agriculture through agri-ecotourism, which is a symbiotic relationship between tourism and agriculture. Making home- or farm stays in agri-ecotourism a subsistence strategy for local youth will contribute to a more prosperous rural economy. Recognising Uttarakhand’s rich culture and heritage while exploring the culinary travel opportunities in homestays will provide opportunities to focus more on traditional food systems, exposing various tangible and intangible aspects of the host region’s food culture to tourists. The findings of this study will aid in identifying specific policy issues for consideration by planners and policymakers at the local and state levels. Additionally, this exploratory study will assist young, motivated researchers in conducting follow-up, in-depth investigations and producing empirical data in their specialised fields.